PENGARUH KUALITAS KEHIDUPAN KERJA, MOTIVASI DAN BUDAYA ORGANISASI TERHADAP KEINGINAN PINDAH KERJA DIMEDIASI OLEH KEPUASAN KERJA (STUDI PADA PEGAWAI HONORER SETDA PROVINSI JAWA TENGAH) - Sudirman, 1242020103 (Jurnal Mahasiswa Pasca Sarjana, 2015)
This research is aimed to describe and analyze the influence of the quality of working life, motivation, and organizational culture to job satisfaction and also the influence of the quality of working life, motivation, and organizational culture to desire to move job due to job satisfaction. Research method which is used is quantitative through census, while primary data are collected through questionnaire.  Population in this research is temporary employees at Regional Secretary of Jawa Tengah Provincial Government, they are 95 personnel. The data collected are then tabulated and data normality tested, and then are analyzed with linier regression analysis with mediation model. This research concludes that quality of working life, motivation, and organizational culture affect positively to job satisfaction; where organizational culture has the strongest impact to job satisfaction, on the other hand quality of working life has the weakest impact to job satisfaction.  Quality of working life, motivation, and job satisfaction affect negatively to desire to move job, while organizational culture does not affect to desire to move job.  Motivation has the strongest impact to desire to move job, while quality of working life has the weakest impact to desire to move job.  Quality of working life, motivation, and organizational culture affect indirectly to job satisfaction.  In other words, it is proven that job satisfaction is the mediation variable. From the conclusion the writer recommends that the temporary employees should be supported with good quality of working life, motivation from their superior, and organizational culture which can stimulate harmoniuos interaction amongst employees, so that it results in job satisfaction where they do not have desire to move job. Keywords: quality of working life, motivation, organizational culture, job satisfaction, and desire to move job.